2011
DOI: 10.4322/actalb.2011.016
|View full text |Cite
|
Sign up to set email alerts
|

Leaf degradation of Salix humboldtiana Willd. (Salicaceae) and invertebrate colonization in a subtropical lake (Brazil)

Abstract: Aim: To evaluate leaf degradation and invertebrate colonization of Salix humboldtiana Willd. in a subtropical shallow lake on the coastal plain of Rio Grande do Sul, Brazil; Methods: Litter bags containing 6.85 g of leaves were incubated in the superficial layer of sediment in the littoral region for 1, 4, 7, 14, 32, 47 and 71 days; Results: After 71 days, a loss of 51% of the initial leaf weight was observed (k = 0.0100 d -1). We estimated that it would take 300 days to lose 95% of the initial weight. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
4
6
1
3
Order By: Relevance
“…However, for the conventional system, this diversity is smaller, and any variation is related to losses in the ecosystem function. Our results on degradation agree with those reported by Telöken et al (2011), which had greatest biomass losses in the initial phase, with a trend to stabilization that extends from the day 32 until the end of the experiment, at day 71. Abundance did not correlate with biomass decay in the systems, but it was significant for the natural wetland, showing that the benthic macroinvertebrates in cultivation areas were probably affected, having Table 3.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…However, for the conventional system, this diversity is smaller, and any variation is related to losses in the ecosystem function. Our results on degradation agree with those reported by Telöken et al (2011), which had greatest biomass losses in the initial phase, with a trend to stabilization that extends from the day 32 until the end of the experiment, at day 71. Abundance did not correlate with biomass decay in the systems, but it was significant for the natural wetland, showing that the benthic macroinvertebrates in cultivation areas were probably affected, having Table 3.…”
Section: Resultssupporting
confidence: 82%
“…Using decomposition bags in a lentic environment, in the southern end of Rio Grande do Sul state, Telöken et al (2011) found a greater abundance of organisms than that found in the present study. However, despite the proximity of the sampled sites, this work was conducted in the winter, while Telöken et al (2011) performed theirs in the autumn with an average temperature of 23.95°C, which may have affected these differences, as well as the differences between the evaluated plant species (Carvalho & Uieda, 2009;Gimenes et al, 2010).…”
Section: Resultscontrasting
confidence: 55%
See 3 more Smart Citations